FORMING OF PILOTS’ RELIABILITY AS A PROBLEM OF THEORETICAL TRAINING AT FLIGHT EDUCATIONAL ESTABLISHMENTS - Смирнова, І. Л. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
This article is devoted to the problem of professional reliability forming of future pilots during professional training and the problems that are associated with it. The author has identified the components of professional reliability and the methods, by which this goal may be achieved during theoretical training in flight educational establishments. The author reviewed the challenges concerning this problem in professional pedagogy during teaching of professional subjects in flight educational establishments